GM-CSF: Orchestrating the Pulmonary Response to Infection - McCormick, Thomas S.; Hejal, Rana B.; Leal, Luis O.; Ghannoum, Mahmoud A. (Frontiers in Pharmacology, 2022)
This review summarizes the structure and function of the alveolar unit, comprised of alveolar macrophage and epithelial cell types that work in tandem to respond to infection. Granulocyte-macrophage colony-stimulating factor (GM-CSF) helps to maintain the alveolar epithelium and pulmonary immune system under physiological conditions and plays a critical role in restoring homeostasis under pathologic conditions, including infection. Given the emergence of novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and global spread of coronavirus disease 2019 (COVID-19), with subsequent acute respiratory distress syndrome, understanding basic lung physiology in infectious diseases is especially warranted. This review summarizes clinical and preclinical data for GM-CSF to treat respiratory infections, and the rationale for sargramostim (yeast-derived recombinant human [rhu] GM-CSF) as adjunctive treatment for COVID-19 and other pulmonary infectious diseases.